Why Try (Not) to Cry: Intra- and Inter-Personal Motives for Crying Regulation - Simons, Gwenda; Bruder, Martin; van der Löwe, Ilmo; Parkinson, Brian (Frontiers in Psychology, 2013)
This article discusses inter- and intra-personal motives for the regulation of crying, and presents illustrative findings from an online survey (N = 110) exploring why and how people regulate crying in their everyday lives. In line with current theorizing on emotion regulation and crying (e.g., Vingerhoets et al., 2000), we propose that emotional crying is regulated using both antecedent-focused techniques targeting the underlying emotion and response-focused techniques targeting the act of crying itself. Indeed, our survey respondents reported having used both antecedent- and response-focused strategies to either up-regulate or down-regulate their crying. Motives for crying regulation may be both inter- and intra-personal and may serve both immediate, pleasure motives and future, utility motives (Tamir, 2009). Our findings suggest that down-regulation attempts are often driven by inter-personal motives (e.g., protecting the well-being of others; impression management) in addition to intra-personal motives such as maintaining subjective well-being, whereas up-regulation attempts are mostly driven by intra-personal motives. Further progress requires methodologies for manipulating or tracking regulation motives and strategies in real-time crying episodes.